CLINICAL ADVANTAGES OF CERAMIC RESTORATIONS MANUFACTURED USING CAD/CAM TECHNOLOGIES - Ranaqulov A.I.,; Salohiddinov M.B., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: In recent years, digital technologies have taken a key role in the development of prosthetic dentistry, providing a high level of accuracy, predictability, and aesthetic quality of prosthetic constructions. Particular attention is given to CAD/CAM technologies, which enable the fabrication of ceramic restorations with a high degree of individualization and minimal influence of the human factor.Ceramic restorations produced using CAD/CAM systems are characterized by optimal mechanical properties, high biocompatibility, and excellent aesthetic performance. The use of digital design and milling allows for precise marginal fit, which is one of the key factors in the longevity of prosthetic constructions and the prevention of secondary caries.